2008
DOI: 10.1080/02640410701579370
|View full text |Cite
|
Sign up to set email alerts
|

The social-cognitive mechanisms regulating adolescents' use of doping substances

Abstract: In this study, we assessed the longitudinal effects of social-cognitive mechanisms on the self-reported use of doping substances and supplements among Italian high school students. In total, 1232 students completed questionnaires measuring various psychological factors hypothesized to influence students' intention to use substances. Three months later, 762 of the students completed the same questionnaires a second time and also reported their use of substances during the time between assessments. Overall, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
221
2
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(258 citation statements)
references
References 31 publications
30
221
2
5
Order By: Relevance
“…The process of moral disengagement has observed in a variety of sporting Final frontier: 8 transgressions (Boardley & Kavussanu, 2007;Corrion, Long, Smith, & d'Arripe-Longueville, 2009;Lucidi, Grano, Leone, Lombardo, & Pesce, 2004;Lucidi et al, 2008), although to our knowledge no peer reviewed study has attempted to examine moral disengagement in the context of studying athletes who have committed doping violations.…”
Section: Moral Disengagementmentioning
confidence: 99%
See 3 more Smart Citations
“…The process of moral disengagement has observed in a variety of sporting Final frontier: 8 transgressions (Boardley & Kavussanu, 2007;Corrion, Long, Smith, & d'Arripe-Longueville, 2009;Lucidi, Grano, Leone, Lombardo, & Pesce, 2004;Lucidi et al, 2008), although to our knowledge no peer reviewed study has attempted to examine moral disengagement in the context of studying athletes who have committed doping violations.…”
Section: Moral Disengagementmentioning
confidence: 99%
“…Additionally, the role of morality, more specifically, 'moral disengagement' was a prominent factor in the decision to dope, but most importantly, the decision to continue to dope. Several moral disengagement mechanisms, as identified by Lucidi et al (2008), emerged during the interviews: advantageous comparison, minimizing or ignoring the consequences, and displaced responsibility. These forms of disengagement served to justify transgressions (i.e., the use of banned substances).…”
Section: The Psychology Of Dopingmentioning
confidence: 99%
See 2 more Smart Citations
“…The sports psychology literature indicates that doping intentions, with athletes considering the pros and cons of the behavior, have mainly been studied from the perspectives of the theory of planned behavior (TPB) [2][3][4][5] and self-determination theory (SDT) [3,4,6,7]. Other studies based on Bandura's [8][9][10] social cognitive theory have shown that affective and resistive self-regulatory efficacy are related directly and/or through moral disengagement to transgressive behaviors in sport [11].…”
Section: Introductionmentioning
confidence: 99%